Mine safety and personal health – in terms of mining accidents and disasters in the Polish coal mining industry - Kapusta, Mariusz; Bąk, Patrycja; Sukiennik, Marta (Frontiers in Earth Science, 2025)
The article concerns one of the most important issues related to occupational safety in Polish hard coal mines. In general, the issue of safety is related to the occurrence of two groups of factors in the extraction process: geological-mining and technical-organizational. Both of these groups cause a number of hazards. Hazards related to the exploitation of minerals from the underground have accompanied miners since the beginning of mining. In the Polish mining industry, over the last 22 years, it can be observed that the number of accidents has decreased by only 1/3. At the same time, the accident frequency index (Wz) increased from 17.31 in 2002 to 27.71 in 2023. Accident monitoring and indicator analysis are key to improving occupational safety conditions and preventing future accidents. The probability of an accident at work in mines is several times higher than the average value obtained for all positions in the economy, especially in Poland, where hard coal is extracted using the underground method. The article presents accident statistics in hard coal mining in Poland since 2002, calculates accident rates, and approximates the accident rate trend for subsequent years. The factors that determine accidents in Polish mines to the greatest extent were also analyzed. The division and mishaps of catastrophes, which unfortunately still occur in the Polish mining industry, were also discussed.